Meta‐analysis of agreement/concordance statistics in studies comparing self‐ vs clinician‐collected samples for HPV testing in cervical cancer screening. Issue 2 (5th March 2022) - Arbyn, Marc; Castle, Philip E.; Schiffman, Mark; Wentzensen, Nicolas; Heckman‐Stoddard, Brandy; Sahasrabuddhe, Vikrant V.
Abstract: We conducted a meta‐analysis of test agreement/concordance between human papillomavirus (HPV) testing in self‐collected vs clinician‐collected samples in 26 studies (10 071 participants) updating a previous meta‐analysis on accuracy for cervical precancer. Pooled overall agreement was 88.7% (95% CI: 86.3%‐90.9%), positive agreement was 84.6% (95% CI: 79.9%‐88.7%), negative agreement was 91.7% (95% CI: 89.1%‐94.0%) and kappa was 0.72 (95% CI: 0.66‐0.78). Subgroup meta‐analyses suggested higher overall agreement for target amplification‐based DNA assays (90.4%) compared to signal amplification‐based DNA assays (86.7%; P = .175) or RNA assays (82.3%; P < .001). HPV test agreement/concordance targets may provide criteria to extend existing validations toward alternative sampling approaches and devices/storage media. Abstract : What's new? Around half of new cervical cancers in the US occur in women who have not had recommended screenings. Self‐sampling for HPV testing may help overcome some barriers to screening access by avoiding the need for a clinic appointment or pelvic exam. Here, the authors conducted a meta‐analysis of test agreement statistics between self‐collected and physician‐collected samples, and found a high level of agreement between the two when looking at pooled parameters of test agreement (overall, positive and negative agreement).